Optimalisasi Potensi Ikan Nila Lokal Melalui Inovasi Bakso Sebagai Strategi Pemberdayaan Ekonomi Berbasis Perikanan Di Kelurahan Pulau Pedalaman - Putri, Laeli; Pebrianti, Wenny; Fitriani, Adelia; Muharani; Wulandari, Suci; Aryanti, Ririn (Universitas KH. Mukhtar Syafaat (UIMSYA), 2025)
The training program on processing tilapia into fish meatballs and its variation (pentol mercon) in Pulau Pedalaman Village, Mempawah Regency, was a collaboration between the KKM-PKM team of the Faculty of Economics and Business, Universitas Tanjungpura, and the official village program entitled Youth Empowerment in Developing Fisheries Innovation. This program aimed to enhance technical skills, creativity, and entrepreneurial motivation among local housewives, young women, and youth by utilizing local fishery potential. The implementation method used a Community Development (CD) approach with stages including preparation, field observation, demonstration-based training, and evaluation. The core participants consisted of 10 people who actively participated in the full practice session, supported by the involvement of youth and village officials. The results showed that all participants were able to apply the fish meatball making techniques, and new product ideas and simple marketing plans emerged. This activity contributed to improving community skills and utilizing tilapia as a home-based business opportunity.